经济转型期的县域财政问题 = County level public finance in China's transition economy - 潘志永 Pan, Zhi Yong (2008)
This paper analyzes China’s country level public finance in the context of economic transition from plan to market, emphasizing in particular on its special features during different time periods. The problems under both the revenue-sharing system and the tax-sharing system, including the potential dangers within the current structure, are studied from the economic, social and institutional perspectives.